Interference - Leth, Jorgen; Gruszynski, Alexander; Jensen, Henning; Uldal, Hanne; Latour, François (Danish Film Institute, 2008)
Though fiction films make up only a small part of Leth's collected works, they hold many telltale signs of Leth's singular approach to documentary cinema. Both "Interference" (1983) and "Traberg" (1992) are set in Haiti and both revolve around the island and a lost, searching male protagonist, who disappears or is pushed from the centre of the fiction. In their place, Haitian reality steps in with a rawness and invasive force that makes the island the central element in the two stories. The director adopts a characteristically hesitant, wait-and-see attitude to his two characters and their actions, even as he unflinchingly explores both their turmoil and the chaos of Haitian reality at hand. The director says: "My whole project and experiment was to have a kind of collapsible fiction that I could take with me, and then have my foreign correspondent's story unfold in a series of real, concrete situations, where reality would be not just a setting but a living co-actor". [www.dfi.dk]
Keywords: DVD-Video